(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the knowledge of nurses in clinical departments about peripheral venous thrombophlebitis at 108 Military Central Hospital from March to April 2024. Method: A survey of 217 nurses from 17 clinical departments was conducted using a quantitative research design and cross-sectional descriptive approach. Data were collected using an online questionnaire based on the tool developed by Lanbeck et al. Result: 81.6% of the surveyed nurses had some knowledge of peripheral venous thrombophlebitis; however, only 18% demonstrated a good understanding. Nurses who had participated in courses or training programs on peripheral venous thrombophlebitis had significantly better knowledge than those who had not. Conclusion: Peripheral venous thrombophlebitis is a common complication of peripheral venous catheterization. Nurses’ knowledge of peripheral venous thrombophlebitis plays a crucial role in clinical practice. Therefore, nursing managers should focus on training to enhance skills in managing peripheral venous catheter care and preventing complications.